ODONATE FAUNA OF KHAJJIAR LAKE (MINI SWITZERTLAND) OF CHAMBA DISTRICT OF HIMACHAL PRADESH, INDIA - SINGH, VIKRAM; H. S. BANYAL (The Bioscan, 2013)
A study of Khajjiar Lake was conducted from June 2008 to March 2012 which revealed the presence of 10 species belonging to 8 genera spread over 5 families of Odonates. It has been analysed that family Libellulidae supported the highest number of species (6 species, under 4 genera) and all other families have been represented by a single species each. Out of these ten eight species belongs to order Anisoptera (dragonflies) and two to Zygoptera (damselflies).